1. `sqrt(16x^4 y^4 z)`

First we will separate the terms.

`==gt sqrt(16x^4y^4z)= sqrt(16) sqrt(x^4) sqrt(y^4) sqrtz)`

Now we will simplify.

`==gt sqrt(16x^4y^4 z)= 4x^2 y^2 sqrtz`

2. `5sqrt(144m4p^4 q^2)`

Separate terms.

`==gt 5sqrt(144 m^4 p^4 q^2) = 5sqrt144 sqrtm^4 sqrtp^4 sqrtq^2`

` ==gt 5sqrt(144m^4p^4q^2) = 5*12 m^2 p^2 q = 60m^2p^2q`

3. `-6sqrt(27m^4 p q^2)`

` = -6sqrt(27)sqrt(m^4) sqrt(p) sqrt(q^2) `

`= -6* 3sqrt3 m^2 q sqrtp `

`= -18sqrt(3p)* m^2 q`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.